Subterranean Types of Endogone Spores in Jobolarangan Forest (Biodiversitas Journal of Biological Diversity, 2016)
Endogone spores are spores produced by Endogone genus of VAM fungi, which are abudant in soil. The objective of the research was to assess the types of Endogone spores found in the soil of Jobolarangan forest. Soil samples were taken based on the dominan vegetation, identification and spores screening were then done to the sample. The result research indicated that there were 5 types of spores, namely: white reticulate, yellow vacuolate, red brown laminate, honey colored sessile, and crenulate.Â© 2001 Jurusan Biologi FMIPA UNS SurakartaKey words: Endogone spores, spore types, Jobolarangan forest